2023
DOI: 10.3390/agronomy13020376
|View full text |Cite
|
Sign up to set email alerts
|

Green Manure Amendment Increases Soil Phosphorus Bioavailability and Peanut Absorption of Phosphorus in Red Soil of South China

Abstract: Peanut (Arachis hypogaea L.) is one of the most important crops produced worldwide. Peanut is the dominant crop in the typical upland red soil areas of China; however, phosphorus bioavailability in red soil is very low, which severely affects peanut production. To improve the phosphorus bioavailability, which substantially promotes the green development of peanut production, a peanut–green manure rotation field experiment was conducted with six treatments (milkvetch; radish; brassica rape; mustard rape; winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The results reported by Crusciol et al (2019) showed that a lower dose of liming (lime 2.7 t ha -1 + gypsum 2.1 t ha -1 ) yielded plant tissue P levels of 0.68%, which was higher than the results of this study in which the treatment of calcite 20 t ha -1 yielded plant tissue level 0.33%, and dolomite 20 t ha -1 yielded at level 0.30%. Gu et al (2023) reported that applying green manure could increase the plant tissue P content up to 0.175%. High plant tissue P content can be supported by increasing the amount of available P in the soil by releasing phosphate ns from the fixation of Al and Fe in the acidic soil and mineralizing organic P (Dasog and Patil, 2007).…”
Section: Effect Of Treatment On Peanut Growthmentioning
confidence: 99%
“…The results reported by Crusciol et al (2019) showed that a lower dose of liming (lime 2.7 t ha -1 + gypsum 2.1 t ha -1 ) yielded plant tissue P levels of 0.68%, which was higher than the results of this study in which the treatment of calcite 20 t ha -1 yielded plant tissue level 0.33%, and dolomite 20 t ha -1 yielded at level 0.30%. Gu et al (2023) reported that applying green manure could increase the plant tissue P content up to 0.175%. High plant tissue P content can be supported by increasing the amount of available P in the soil by releasing phosphate ns from the fixation of Al and Fe in the acidic soil and mineralizing organic P (Dasog and Patil, 2007).…”
Section: Effect Of Treatment On Peanut Growthmentioning
confidence: 99%
“…This bicarbonate can solubilize soil mineral P, ensuring sufficient phosphorus for subsequent crops" [64,65] "Addition of green manures increase the soil organic carbon subsequently leading forward to reduction on soil pH. This decrease in soil pH reduces the phosphate fixation in soil with iron and aluminium" [66]. "Ultimately availability of phosphous increases.…”
Section: Fig 5 Soil Enrichment With N By Fixation and Mineralization ...mentioning
confidence: 99%
“…Soil total nitrogen content (TN) was digested in a sulfuric acid-hydrogen peroxide solution and tested by the Kjeldahl method with an automatic Kjeldahl nitrogen analyzer (KDY-9820, KETUO, Beijing, China) [46]. Soil available phosphorus (AP) concentration was extracted using sodium bicarbonate and measured through the vanadium molybdate yellow colorimetric method with a spectrophotometer (Model 722, Modern Science Ltd., Shanghai, China) [47]. Soil-available potassium (AK) was extracted by ammonium acetate and tested following the flame photometer method (6400A, Precision Scientific Instrument Co., Ltd., Shanghai, China) [48].…”
Section: Soil Physicochemical Properties and Nutrient Contentmentioning
confidence: 99%